Intra-Orbital Meningioma Causing Loss of Vision in Neurofibromatosis Type 2: Case Series and Management Considerations - Lekovic, Gregory P.; Schwartz, Marc S.; Hanna, George; Go, John (Frontiers in Surgery, 2018)
Objectives: Little evidence exists regarding the management of orbital meningioma causing vision loss in the setting of neurofibromatosis Type 2 (NF2). We review here our experience with patients at risk for blindness due to intra-orbital meningioma. Design/Setting/Participants/Main Outcome Measures: The charts of patients with NF2 presenting for evaluation of intra-orbital meningioma and vision impairment between 2008 and 2013 were retrospectively reviewed in accordance with institutional IRB policies. Patients with primarily extra-orbital tumors and minimal intra-orbital extension were excluded. Charts were analyzed for the presence and/ or imaging progression of intra-orbital tumor, presence of other optic apparatus pathology, presence and/ or progression of vision impairment, and intervention performed (if any). Results: Seven patients with intra-orbital meningioma on MRI and bilateral vision loss and/or unilateral visual impairment due to tumor and contralateral blindness of any etiology were identified. Patients without salvageable vision in either eye were excluded (n=3). Diagnosis of meningioma was obtained either by biopsy or based on imaging assessment. Conclusion: Conservative management of orbital tumors in NF2 may be preferred in asymptomatic patients but may not be acceptable in patients with progressive visual decline. Radiation is a reasonable option for meningiomas of the orbit and optic nerve sheath. Finally, although the benefit of cranial nerve decompression in NF2 for preservation of facial nerve and hearing has previously been established, the role of optic nerve decompression for preservation of vision in NF2 remains poorly defined.